A surrogate model based on sparse grid interpolation for boiling water reactor subchannel void distribution. (September 2019) - Bennett, Alexander; Martin, Nicolas; Avramova, Maria
Highlights: Created a surrogate model for the prediction of the subchannel void distribution. The computational time was reduced from minutes to about a second. The surrogate model reproduced the high fidelity model with low errors. The surrogate model is coupled with a lattice physics code to provide feedback. Abstract: Boiling water reactors are simulated using nodal diffusion core simulators which rely upon homogenized and condensed cross sections from a lattice physics code. In the lattice calculation, the void distribution is typically assumed to be uniform in the radial direction. To remove this assumption, a thermal hydraulic code can be coupled with a lattice physics code to include a radial void distribution in the cross sections. To minimize the additional computational costs, a surrogate model can be generated for the thermal hydraulic code. In this research, a surrogate model is generated for the thermal hydraulic code F-COBRA-TF using sparse grid interpolation. The surrogate model is tested on how well it can reproduce the F-COBRA-TF void distribution for various conditions on the ATRIUM 10 assembly. The surrogate model is found to be effective at reproducing the F-COBRA-TF void distribution and reducing the computational costs from the order of minutes to about a second. A coupling is created between the surrogate model and the lattice physics code APOLLO2-A. Including the void distribution in the lattice physics calculation is found to have a large effect on the gadolinium worth.